New data on Jurassic Sinoalidae from northeastern China (Insecta, Hemiptera). (17th July 2017) - Chen, Jun; Zheng, Yan; Wei, Guangjin; Wang, Xiaoli
Abstract: The Sinoalidae, as one of the three Mesozoic froghopper families, was recently recognized from the latest Middle–earliest Late Jurassic Daohugou Biota of northeastern China. We herein report some new materials from the same horizon and locality, providing some new insights on morphological diversity and evolution of this family. Shufania hani new genus new species indicates that the relative branching position of veins M and CuA of the forewing is highly variable within the Sinoalidae and not appropriate for family-level diagnosis. The venations of three reported sinoalid hind wings are conservative, likely due to its simplified topology and reduced terminal branches. Color patterns of hind wings are likely variable for different sinoalid froghoppers. However, considering that color pattern is easily weakened or even erased by diagenetic processes for imprint fossils, the morphological character is not reliable for distinguishing different sinoalid taxa. Additionally, our new material suggests that the number of lateral spines of the hind tibia can vary intra-individually for sinoalids, just as in some recent froghoppers.